Inhibition of hydrogen peroxide, nitric oxide and TNF-alpha production in peritoneal macrophages by ethyl acetate fraction from Alchornea glandulosa - Lopes, FCM; Calvo, T. R.; Vilegas, Wagner [UNESP]; Carlos, I. Z. (Pharmaceutical Soc Japan, 2005)
The effects of Alchornea glandulosa ethyl acetate fraction (AGF) on hydrogen peroxide (H2O2), nitric oxide (NO) and tumor necrosis factor-alpha (TNF-alpha) production in peritoneal macrophages activated with lipopolysaccharide (LPS) or phorbol myristate acetate (PMA) were investigated. Analysis by thin layer chromatography (TLC) of AGF showed several constituents, including flavonoids, which may have anti-inflammatory activity. Inhibitory effects of the fraction in H2O2 and NO production ranged from 8.59 +/- 7.84% to 70.56 +/- 4.16% and from 16.06 +/- 3.65% to 38.73 +/- 3.90%, respectively. The TNF-alpha production was only partially inhibited in the tested concentrations (12.21 +/- 6.23%-15.16 +/- 0.96%). According to these results, it is suggested that AGF has anti-inflammatory activity. This medicinal plant may have therapeutic potential in the control of inflammatory disorders.
Keywords: Alchornea glandulosa; anti-inflammatory activity; flavonoid; hydrogen peroxide; nitric oxide; TNF-alpha